2012
DOI: 10.1103/physrevb.85.174423
|View full text |Cite
|
Sign up to set email alerts
|

Combined analytical and numerical approach to magnetization plateaux in one-dimensional spin tube antiferromagnets

Abstract: In this paper, we investigate the properties of frustrated three-leg spin tubes under a magnetic field. We concentrate on two kind of geometries for these tubes, one of which is relevant for the compound [(CuCl2tachH)3Cl]Cl2. We combine an analytical path integral approach with a strong coupling approach, as well as large-scale Density Matrix Renormalization Groups (DMRG) simulations, to identify the presence of plateaux in the magnetization curve as a function of the value of spin S. We also investigate the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
4
12
0
Order By: Relevance
“…We therefore conclude that the ground state is characterized by TLL1 of a chirality XY model consistent with the previous work by Plat et al 11) The local spin magnetization S z i, j of the above ground state is shown in Fig. 6 (b).…”
Section: J /J ⊥ 10supporting
confidence: 91%
See 1 more Smart Citation
“…We therefore conclude that the ground state is characterized by TLL1 of a chirality XY model consistent with the previous work by Plat et al 11) The local spin magnetization S z i, j of the above ground state is shown in Fig. 6 (b).…”
Section: J /J ⊥ 10supporting
confidence: 91%
“…Since the spin excitation has a gap in the magnetization plateau, the low energy massless excitation of Eq. 5 is described by chirality 11) whose Hamiltonian is…”
Section: J /J ⊥ 10mentioning
confidence: 99%
“…In our case, in addition to the basic triangular geometry of the nanotube, the competition between J // and J ⊥ with opposite signs is indeed at the origin of the frustration giving rise to the magnetizing plateaus. Similar effects have been demonstrated in a triangular spin-½ tubes by using a combination of an integrated analytical pathway model with a strong coupling approach, as well as large-scale simulations of density matrix renormalization groups (DMRG) [30].…”
Section: Isothermal Magnetizationmentioning
confidence: 53%
“…Similar magnon-crystal ground states are present in other frustrated quantum spin system in one-, two-, and three-dimensional systems 43 . Our results are the semiclassical description of the exactly factorized ground state for general spin S, as has been done in some frustrated quantum spin chains 44,45 .…”
Section: Dominant Inter-layer Couplingmentioning
confidence: 55%